(untitled) (Journal of the College of Education for Women, 2022)
Writing in English language demands both mental skills and a suitable level of language proficiency. Some studies showed that writing anxiety has an impact on the acquisition of language learning. This study; however, teaches the cognitive strategies (PLAY & WRITE) as a writing strategy, so as to decrease students’ use of it when experiencing writing anxiety at the academic writing level. The sample has been (100) second-stage Department of English learners at the College of Education (Ibn –Rushd), in the University of Baghdad-Iraq. They have been randomly selected and divided into experimental and control groups; (50) students in each group. To achieve the objective of the study, SLWAI questionnaire has been distributed to the experimental group, who has been taught the writing strategies. Each student has to writte a minimum of 100-word essay topic once per week for 15 weeks. As for the control group, it has been taught using the conventional way. The hypothesis states that there is no effect of using the PLAN and WRITE Strategies on the Iraqi EFL College Students’ Writing Anxiety. The instrument incorporated a SLWAI questionnaire that has been adopted from Cheng (2004). The pre-and post-questionnaire information has been analyzed using (SPSS). Essay writing strategies has found to have positive effects on decreasing the writing anxiety of the trial team. Furthermore, the composition strategies (PLAY & WRITE) facilitate the writing environments and decrease the tensions of students when writing a composition.